2017
DOI: 10.1186/s12955-017-0758-x
|View full text |Cite
|
Sign up to set email alerts
|

Employment status and health related quality of life among Hodgkin-lymphoma survivors’– results based on data from a major treatment center in Hungary

Abstract: BackgroundDue to risk and response adapted treatment strategies, more than 80% of newly diagnosed classical Hodgkin lymphoma (HL) patients can be cured, and become long-term survivors. However, a high proportion of survivors suffer from treatment-related long-term side effects such as secondary malignancy, organ failure, persistent fatigue and psychological distress. The aim of this study was to evaluate psychological distress and its risk factors among our HL survivors.MethodsOne hundred sixty-three (50% fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…With respect to employment status, the findings in this study were in line with the results in several early [59][60][61][62]. Clinically, employment was associated with QoL in multiple sclerosis patients [63], HRQoL among people with multiple sclerosis [64], HRQoL among people with schizophrenia [65], and HRQoL among Hungarian Hodgkin lymphoma survivors [66]. Thus, the associations could be generalized.…”
Section: Discussionsupporting
confidence: 86%
“…With respect to employment status, the findings in this study were in line with the results in several early [59][60][61][62]. Clinically, employment was associated with QoL in multiple sclerosis patients [63], HRQoL among people with multiple sclerosis [64], HRQoL among people with schizophrenia [65], and HRQoL among Hungarian Hodgkin lymphoma survivors [66]. Thus, the associations could be generalized.…”
Section: Discussionsupporting
confidence: 86%
“…An online survey in 153 MEN1 patients who are part of the American MEN support group revealed that this group experienced significant financial burden and unemployment, which were both correlated to worse HRQOL [17]. A similar effect of employment on HRQOL is observed in different malignancies [21]. In addition, in a MEN2 cohort, a higher physical functioning score was observed in actively working patients than in inactive subjects [19].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective international study showed that employment loss was prospectively associated with poorer mental HRQoL [98]. Clinically, employment was associated with QoL in multiple sclerosis patients [99], HRQoL among people with multiple sclerosis [100], HRQoL among people with schizophrenia [101], and HRQoL among Hungarian Hodgkin lymphoma survivors [102].…”
Section: Discussionmentioning
confidence: 99%